Correlation of civil legal principles and civil procedural in Ukrainian legislation - Сафончик, Оксана Іванівна; Сафончик, О. І.; Сафончик, Оксана Ивановна; Safonchyk, Oksana I.; Діденко, Лариса Василівна; Діденко, Л. В.; Диденко, Лариса Васильевна; Didenko, Larysa V.; Денисяк, Наталя Миколаївна; Денисяк, Н. М.; Денисяк, Наталья Николаевна; Denysiak, Natalia M. (Universidad del Zulia, 2021)
Civil legal and civil-procedural legal relations are one of the most significant categories in the science of civil and civil-procedural law, the relationship of which is not fully studied in science, so it is necessary to reveal the essence of their correlation and find differences between them. In the legal doctrine, there is a small number of works that would reveal the content of the relationship of such legal relations, the algorithm and criteria for their comparison are not fully developed, the scientific approaches to the separation of the criterion of their comparison are not revealed. In this regard, it is necessary to fulfil the doctrinal study of civil legal and civil procedural legal relations, both separately and jointly, using a particular criterion. The following methods were used in the study of the relationship between civil legal and civil-procedural legal relations: formal-legal, generalization, method of analysis of normative documents, articles and monographs, comparative legal method. As a result of the research, the connections between such categories as civil legal relations and civil procedural legal relations were clarified, and the criteria for their comparison were singled out.

Цивільно-правові та цивільно-процесуальні правовідносини є однією з найбільш значущих категорій у науці цивільного та цивільно-процесуального права, взаємозв’язок яких у науці до кінця не досліджений, тому необхідно розкрити сутність їх співвідношення та знайти відмінності між ними. У правовій доктрині є невелика кількість праць, які б розкривали зміст взаємозв’язку таких правовідносин, алгоритм і критерії їх порівняння розроблені не повністю, наукові підходи до виокремлення критерію їх порівняння не виявлені. У зв’язку з цим необхідно провести доктринальне дослідження цивільно-правових та цивільно-процесуальних правовідносин як окремо, так і спільно, за певним критерієм. При дослідженні співвідношення цивільних правових і цивільно-процесуальних правовідносин використовувалися такі методи: формально-правовий, узагальнюючий, метод аналізу нормативних документів, статей і монографій, порівняльно-правовий метод. У результаті дослідження з’ясовано зв’язки між такими категоріями, як цивільні правовідносини та цивільні процесуальні правовідносини, виділено критерії їх порівняння.
Safonchyk O. Correlation of civil legal principles and civil procedural in Ukrainian legislation / O. Safonchyk, L. Didenko, N. Denysiak // Cuestiones Politicas. - Vol. 39. – Iss. 69. - Universidad del Zulia, 2021. – Р. 475-491.
Keywords: civil legal relations; civil-procedural legal relations; relation of concepts; characteristics of legal relations; scientific approaches; цивільні правовідносини; цивільно-процесуальні правовідносини; співвідношення понять; характеристика правовідносин; наукові підходи; Research Subject Categories::LAW/JURISPRUDENCE